Emotions of University Student Teachers Towards Learning English from a Literacy Perspective (2023)
This research project aimed to analyze the emotions of a group of Mexican student teachers towards learning English from a literacy perspective. The participants were 90 students of the bachelor's degree in foreign languages of the B1 course of English at the University of Colima in Mexico; the methodology implemented was a case study. The data were collected through three instruments: a questionnaire, observation guides and a descriptive inventory of literacy materials. As a result of this research, we found that the adequate use of different literacy strategies and materials generates a positive emotional response from students and contributes to their English learning process. Further, there is a relationship between the literacy materials supplied by schools and the literacy strategies implemented by teachers in the English classroom. Finally, we draw some conclusions about the use of literacy materials and strategies and students' emotions in the English learning process and made some recommendations on how to approach future research on this topic.